Efektivitas Cognitive Behavioral Therapy (CBT) dan Eye Movement Desensitization and Reprocessing (EMDR) dalam Mereduksi Trauma Pelecehan Masa Kecil pada Remaja Perempuan: Studi Kasus Lima Sesi Konseling: Efektivitas Cognitive Behavioral Therapy (CBT) dan Eye Movement Desensitization and Reprocessing (EMDR) dalam Mereduksi Trauma Pelecehan Masa Kecil pada Remaja Perempuan: Studi Kasus Lima Sesi Konseling - mia yanti; Dian Mustika Maya (Universitas Veteran Bangun Nusantara, 2026)
This study aims to examine the effectiveness of combining Cognitive Behavioral Therapy (CBT) and Eye Movement Desensitization and Reprocessing (EMDR) in reducing trauma associated with childhood sexual abuse in adolescent females. A single qualitative case study design was employed, involving a 20-year-old female university student (initials L.S.A.) who had experienced sexual abuse during elementary school. The intervention was conducted over five counseling sessions, each lasting 45 minutes. Data collection involved behavioral observation during sessions, recordings of the counseling process, and documentation of counseling session plans (RPL). The results indicate that the integrative CBT-EMDR approach successfully helped the client—step by step—to identify and restructure negative thoughts, reprocess traumatic memories, and develop adaptive coping strategies. By the end of the fifth session, the client demonstrated a significant reduction in anxiety, an ability to express feelings openly, and a more positive sense of self-acceptance. These findings support the use of integrative CBT-EMDR as an effective intervention for counseling adolescents who are victims of sexual abuse. The study concludes that counseling services utilizing the Cognitive Behavioral Therapy and Eye Movement Desensitization and Reprocessing approach are capable of alleviating trauma in adolescent victims of sexual abuse.